2020
DOI: 10.1007/s11356-020-11447-y
|View full text |Cite
|
Sign up to set email alerts
|

Production of zeolitic materials in pilot scale based on coal ash for phosphate and potassium adsorption in order to obtain fertilizer

Abstract: The use of different types of zeolites (X, Na-P1, and 4A) synthesized by different methods and scales were tested in this work to adsorb nutrients present in synthetic solutions and industrial effluents for later application as fertilizer. Modifications with calcium chloride were performed on the zeolite with the best performance to increase its adsorption capacity. The best performing zeolite was type X (ZXH) produced on a pilot scale by the hydrothermal process. Its adsorption capacity without modification w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
(95 reference statements)
0
5
0
Order By: Relevance
“…The final potassium concentrations of these tests were analyzed by atomic absorption spectrometry (AAS), Varian equipment, and model AA240FS. The Lagergren’s integrated model of pseudo-first-order (eq ), pseudo-second-order (eq ), and the intraparticle diffusion model proposed by Weber and Morris (eq ) were applied to the data, for the initial conditions of q = 0 and t = 0. , q t = q e false( 1 exp ( k 1 t ) ) q t = q e 2 k 2 t 1 + q e k 2 t q t = k id t + C where q t is the potassium adsorption capacity (mg/g), q e is the potassium adsorption capacity at equilibrium (mg/g), t is the time (min), k 1 is the rate constant (min –1 ), k 2 is the constant of pseudo-second-order rate (g·mg –1 ·min –1 ), k id is the intraparticle diffusion rate constant (mg·g –1 ·min –0.5 ), and C is the initial adsorption capacity (intersection with the q t axis) (mg/g).…”
Section: Methodsmentioning
confidence: 99%
“…The final potassium concentrations of these tests were analyzed by atomic absorption spectrometry (AAS), Varian equipment, and model AA240FS. The Lagergren’s integrated model of pseudo-first-order (eq ), pseudo-second-order (eq ), and the intraparticle diffusion model proposed by Weber and Morris (eq ) were applied to the data, for the initial conditions of q = 0 and t = 0. , q t = q e false( 1 exp ( k 1 t ) ) q t = q e 2 k 2 t 1 + q e k 2 t q t = k id t + C where q t is the potassium adsorption capacity (mg/g), q e is the potassium adsorption capacity at equilibrium (mg/g), t is the time (min), k 1 is the rate constant (min –1 ), k 2 is the constant of pseudo-second-order rate (g·mg –1 ·min –1 ), k id is the intraparticle diffusion rate constant (mg·g –1 ·min –0.5 ), and C is the initial adsorption capacity (intersection with the q t axis) (mg/g).…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that wheat and maize yield increased by 16.0% and 35.0%, respectively under the combination of the treatments, when compared to crops grown on unamended soil, irrigated with lower leaching fraction and planted using conventional methods. Bonetti et al (2021) synthesized zeolites type X from coal ash, loaded them with macronutrients such as phosphorus and potassium, and applied them as fertilizers in the cultivation of Tagetes patula. Results showed that the leaching of nutrients occurred gradually, being available during the entire period of plant development.…”
Section: Zeolites In Agriculture Applicationsmentioning
confidence: 99%
“…Bonetti et al. (2021) synthesized zeolites type X from coal ash, loaded them with macronutrients such as phosphorus and potassium, and applied them as fertilizers in the cultivation of Tagetes patula. Results showed that the leaching of nutrients occurred gradually, being available during the entire period of plant development.…”
Section: Zeolites In Agriculture Applicationsmentioning
confidence: 99%
See 2 more Smart Citations